THE MEDIATING ROLE OF INDUSTRIAL WORK PRACTICE ON THE INFLUENCE OF SELF-EFFICACY AND TEACHER SUPPORT ON ENTREPRENEURIAL INTENTIONS AT VOCATIONAL HIGH SCHOOLS IN SEMARANG CITY - Euis Rachmawati Azizah; Rusdarti; Amir Mahmud (Universitas Negeri Semarang, 2026)
The high unemployment rate of vocational high school graduates in Semarang City proves that students' entrepreneurial intentions have not developed optimally, so it is necessary to understand the factors that influence it, especially self-efficacy, teacher support, and Industrial Internship experience. This study aims to analyze the influence of self-efficacy and teacher support on vocational high school students' entrepreneurial intentions, with Industrial Internship as a mediating variable. This study aims to analyze the impact of self-confidence (self-efficacy) and teacher support on vocational high school students' entrepreneurial interests, by placing Industrial Internship (Prakerin) experience as a mediating variable. The method used is a non-experimental quantitative approach, where data were collected through distributing questionnaires to 216 respondents from grade XII students at SMKN Semarang City. Statistical analysis was carried out using path analysis techniques, supported by t-tests, coefficients of determination, and Sobel tests using SPSS software. The research findings reveal that both self-efficacy and teacher support have a positive and significant influence in shaping entrepreneurial intentions, both directly and indirectly. Furthermore, Industrial Internships were shown to function as a mediator, strengthening the relationship between the two independent variables and entrepreneurial intentions. The implications of this study emphasize the need to improve students' personal competencies, optimize the role of educators, and provide quality industrial internship experiences to foster an entrepreneurial spirit among SMKN students in Semarang City, particularly in the areas of Online Business and Marketing.